Model Praktik Manajemen Keuangan Pribadi Berbasis Literasi Keuangan, Orientasi Masa Depan dan Kecerdasan Spiritual pada Generasi “Y” Di Kota Medan - Sri Fitri Wahyuni; Radiman Radiman; Jufrizen Jufrizen; Muhammad Shareza Hafiz; Ade Gunawan (Politeknik Ganesha Medan, 2022)
Personal financial management practices are generally used by people for a process of dealing with their financial needs. Usually the practice of personal financial management is assessed through an attitude, character, and financial behavior of a person which includes the level of personal debt, assistance in the stock market, the ability to be effective in handling or increasing wealth, and the ability to calculate assets at a relatively low cost. This research has a specific objective, namely to study the factors that influence the Personal Financial Management Practices of Generation Y in Medan City and produce a Personal Financial Management Practice Model Based on Financial Literacy, Future Orientation and Spiritual Intelligence in Generation Y in Medan City. This research is a basic research (basic research). The population in this study were all students in some of the best private universities in North Sumatra. To determine the sample size, the use of Maximum Likelihood estimation in the Structural Equation Model (SEM) is 100-200 samples, so the researcher will take a sample of 100-200 respondents in order to fulfill one of the requirements of the data analysis method using SEM. Thus the sample of this study was taken as many as 150 students as research samples. The data analysis technique used in this research is by using Structural Equation Modeling (SEM) with the help of PLS. The results of the study indicate that future orientation has a negative and insignificant effect on personal financial management practices in Generation Y in Medan City. Financial literacy has a positive and significant effect on personal financial management practices in Generation Y in Medan City. Spiritual intelligence which moderates future orientation and financial literacy on personal financial management practices has a positive effect on future orientation, but has a negative effect on financial literacy and the two variables moderated by spiritual intelligence are not significant on personal financial management practices in Generation Y in Medan City .